A monograph of the Afrotropical Cassidinae (Coleoptera: Chrysomelidae). Part 4. Revision of the genus Chiridopsis Spaeth - Borowiec, Lech; Świętojańska, Jolanta (Zootaxa, 2017)
African members of the genus Chiridopsis Spaeth, 1922 are revised and 32 species are recognized in this area. Three species are described as new: Chiridopsis klapperichi n.sp. (Republic of South Africa), Chiridopsis tanzaniensis n.sp. (Tanzania) and Chiridopsis zambiana n.sp. (Zambia). The following new synonyms are proposed: Chiridopsis aequinoctialis (Olivier, 1808) = Coptocycla kraatzi Wagener, 1880 syn. nov.; Chiridopsis aubei (Boheman, 1855) = Chiridopsis weisei Spaeth, 1924 syn. nov.; Chiridopsis boutareli (Spaeth, 1917) = Chirida subgibbosa Spaeth, 1917 syn. nov.; Chiridopsis flavipennis (Spaeth, 1902) = Chiridopsis rothschildi Spaeth, 1922 syn. nov.; Chiridopsis nigrosepta (Fairmaire, 1891) = Coptocycla vernicata Fairmaire, 1891 syn. nov. = Cassida circumcincta Weise, 1919 syn. nov.; Chiridopsis observabilis (Spaeth, 1916) = Chiridopsis athinia Spaeth, 1924 syn. nov. Lectotypes are designated for Chirida ariadne Weise, 1896, Chirida circe Weise, 1896, Chirida observabilis Spaeth, 1916 and Chirida tessellata Spaeth, 1917. Colour photos of species, including intraspecific variablity, key to species and maps of distribution are given.